Effects of Panax ginseng extract in practical diets for rainbow trout (Oncorhynchus mykiss) on growth performance, immune response and resistance to Yersinia ruckeri. (20th April 2016) - Bulfon, Chiara; Bongiorno, Tiziana; Messina, Maria; Volpatti, Donatella; Tibaldi, Emilio; Tulli, Francesca
Abstract: In a preliminary in vitro study, a Panax ginseng extract exhibited an evident antibacterial activity against Yersinia ruckeri and Lactococcus garvieae and affected the respiratory burst and proliferation of rainbow trout Oncorhynchus mykiss leukocytes. Subsequently, the effects of a dietary ginseng extract supplementation on growth, blood biochemical profile, innate immune response and resistance against Y. ruckeri infection were investigated in vivo in rainbow trout juveniles. Four experimental diets were obtained by adding 0.0%, 0.01%, 0.02%, 0.03% of ginseng ethanolic extract to a commercial feed. Each diet was fed to triplicate groups of fish (mean body weight 30.5 ± 0.15 g) at 1% of body weight day −1 for 10 weeks. The dietary supplementation with ginseng extract did not affect growth performance, feed utilization, biometric traits and fish whole body composition ( P > 0.05). No major changes due to graded levels of ginseng extract in the diet were observed in blood biochemical parameters except for increasing plasma triglycerides and non‐esterified fatty acids in fish fed diets including 0.01% and 0.02% of extract ( P < 0.05). The innate immune response was barely modulated by the dietary addition of ginseng extract. Serum lysozyme and leukocytes respiratory burst activities were just slightly increased in fish fed all the ginseng extract‐supplemented diets compared with controls, whereas serum antiproteases and leukocyte MPO were not affected ( P > 0.05). The dietary administration of ginseng extract induced a reduction in mortality of rainbow trout infected with Y. ruckeri, although no significant differences between treated and control groups were observed ( P > 0.05).